The Role of Interpersonal Communication of Teachers in Enhancing Students' Learning Motivation at SDN Singonegaran 1 Kota Kediri - Mirna Sari Rahayu Mirna; Prima Ayu Rizqi Mahanani; Mohammad Arif (Nusantara Society Lab, 2025)
A study at SDN Singonegaran 1 Kota Kediri explored the role of teachers' interpersonal communication in boosting students' learning motivation. Using a qualitative descriptive approach, researchers interviewed four teachers and conducted observations and documentation. The study was based on Joseph A. DeVito's theory, focusing on five key indicators: openness, empathy, supportiveness, positiveness, and equality. The findings showed that teachers' interpersonal communication is crucial for enhancing student motivation. Teachers employed interactive techniques like ice-breaking, trigger questions, and digital media (e.g., Kahoot!) to create a comfortable learning environment. They also used positive reinforcement like praise and points to reward students. The communication process included building trust, providing clear verbal and nonverbal messages, using supportive media, and giving positive feedback. Additionally, teachers tailored their approach to each student's unique needs. While these strategies were effective, challenges such as student shyness and lack of confidence remained. The study concluded that effective teacher communication significantly improves student motivation and creates a supportive classroom atmosphere. It recommends that teachers receive continuous training to refine their communication skills and overcome these barriers, thereby promoting students' academic and personal growth.